THE EFFECT OF MULTIMEDIA USE ON UNDERSTANDING CONCEPT OF PG-PAUD STUDENTS IN COURSE COGNITIVE DEVELOPMENT AND CREATIVITY OF EARLY CHILDHOOD IN UNSRI PALEMBANG - Hasmalena Hasmalena; Rukiyah Rukiyah; Mahyumi Rantina (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2018)
Abstract:. The Effect of multimedia usage on PG-PAUD student concept understanding in cognitive development and creativity course of early childhood has been done on PG-PAUD Student semester three in Palembang Sriwijaya University. The type of research used is experiment with One Shoot Case Study descriptions, with sampling technique that is purposive sampling. The sample in the pre-experiment class is 27 and the post-test class is 28. The data collection technique is written essay, interview and documentation. Result of data analysis obtained is 80,71, while result of hypothesis test based on t-test obtained t_count t_table or got t_count = 6,76 t_table = 4,83, hence Ho refused and Ha accepted, thus there effect multimedia usage to understanding the concept of PG-PAUD students in courses of cognitive development and creativity of early childhood. With assessment indicators Redefining a concept, Classifying objects according to certain traits according to their concepts, Providing examples of concepts, Using, utilizing and selecting specific procedures. So the use of multimedia to understanding the concept of the students is very influential to improve understanding of the concept..Keyword: Multimedia Usage, Conceptual Understanding, Early Childhood Education Abstrak: Pengaruh penggunaan multimedia pada pemahaman konsep siswa PG-PAUD dalam perkembangan kognitif dan kreativitas anak usia dini telah dilakukan pada mahasiswa PG-PAUD semester tiga di Universitas Sriwijaya Palembang. Jenis penelitian yang digunakan adalah eksperimen dengan deskripsi One Shoot Case Study, dengan teknik pengambilan sampel yaitu purposive sampling. Sampel dalam kelas pra-eksperimen adalah 27 dan kelas post-test adalah 28. Teknik pengumpulan data adalah esai tertulis, wawancara dan dokumentasi. Hasil analisis data yang diperoleh adalah 80,71, sedangkan hasil uji hipotesis berdasarkan t-test diperoleh t_count t_table atau mendapat t_count = 6,76 t_table = 4,83, maka Ho ditolak dan Ha diterima, sehingga ada pengaruh penggunaan multimedia. untuk memahami konsep siswa PG-PAUD dalam kursus pengembangan kognitif dan kreativitas anak usia dini. Dengan indikator penilaian Mendefinisikan kembali konsep, mengklasifikasikan objek sesuai dengan sifat-sifat tertentu sesuai dengan konsep mereka, Memberikan contoh konsep, Menggunakan, memanfaatkan dan memilih prosedur tertentu. Jadi penggunaan multimedia untuk memahami konsep siswa sangat berpengaruh untuk meningkatkan pemahaman konsep tersebutKata Kunci: Pemanfaatan multimedia, Pemahaman konsep, PAUD.